Getting the transport right - for what? : What transport policy can tell us about the construction of sustainability. - Rehnlund, Mathilde; Hassler, Björn; Björklund, Fredrika; Mukhtar-Landgren, Dalia (2019)
This thesis studies transport as a governing tool that shapes the physical environment and human society, as well as having environmental impacts.